Assessment of Water Quality in the Tributaries of the Rega River (Northwestern Poland) as a Fish Habitat - Małgorzata Bonisławska; Arkadiusz Nędzarek; Adam Tański; Agnieszka Tórz; Krzysztof Formicki (Applied Sciences)
The effective assessment and improvement of water quality require analysis not only of the main river flowing into the sea but also of its tributaries, which may contribute to significant pollution. This study aimed to evaluate the physicochemical conditions of water in nine streams flowing into the Rega River between 2018 and 2022. It also sought to determine whether the water quality in these tributaries meets the standards defined by EU regulations for inland waters that serve as habitats for fish. The parameters analyzed included water temperature, dissolved oxygen (DO), pH, total suspended solids (TSSs), electrical conductivity (EC), alkalinity, total hardness (TH), biochemical oxygen demand (BOD5), nitrite nitrogen (NO2−-N), ammonium nitrogen (NH4+-N), and total phosphorus (TP). The results indicated that most indicators met the requirements for waters suitable for salmonid species. Elevated concentrations of NO2−-N observed across all sites were still within acceptable limits for cyprinid species. Among the parameters studied, TSSs was identified as the main factor that downgraded water quality over the study period. Principal component analysis (PCA) showed that the dominant variables influencing water chemistry were NH4+-N, NO2−-N, TP, EC, and chloride (Cl−), all of which are associated with anthropogenic sources.